Determinants of Foreign Investment on Economic Growth in North Sumatra Province - Suwitra, Irshadi Fariz; Batubara, Maryam; Arif, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to look at the determinants of foreign investment on economic growth in North Sumatra province from 2011 to 2023. The variables of foreign investment determinants are inflation, minimum wage, and labor. Data collection techniques using secondary data, namely annual reports published by the government, data analysis techniques using panel data tests, model suitability tests, panel data regression common effect models (CEM), multicollinearity tests, heteroscedasticity tests, t-tests, F tests, and determination coefficients processed with Eviews 9 software. The results of this study indicate that the determinants of foreign investment partially with the inflation variable do not affect economic growth, the minimum wage variable has a negative and significant effect on economic growth by 1.58 percent, the labor variable has a positive and significant impact on economic growth by 1.25 percent and simultaneously the determinants of foreign investment have a positive and significant effect on economic growth with a contribution of 35.16 percent.